Effects of Locally Administered Tiludronic Acid on Experimental Periodontitis in Rats. Issue 9 (1st September 2014) - Furlaneto, Flávia A.C.; Nunes, Nara L.T.; Oliveira Filho, Ivan L.; Frota, Nicolly P.R.; Yamamoto, Kely O.; Lisboa, Mario R.P.; Ervolino, Edilson; Taba, Mario; Rêgo, Rodrigo Otávio; Messora, Michel R.
Abstract : Background: It appears there are no studies evaluating the influence of the bisphosphonate tiludronic acid (TIL) on periodontitis. The purpose of this study is to evaluate via microtomographic, histopathologic, histometric, and immunohistochemical analyses the effects of local administration of TIL on ligature‐induced periodontitis in rats. Methods: Forty‐eight rats were divided into six groups: C (control), EP (experimental periodontitis), EP‐Saline, EP‐TIL0.1, EP‐TIL0.3, and EP‐TIL1. In EP, a ligature was placed around maxillary second molars. In EP‐TIL0.1, EP‐TIL0.3, and EP‐TIL1, TIL solutions of 0.1, 0.3, and 1 mg/kg body weight, respectively, were injected into the subperiosteal palatal area adjacent to maxillary second molars every other day. EP‐Saline received 0.9% NaCl solution instead. Animals were euthanized at day 11. Bone changes were evaluated by microtomographic and histometric analyses. Histopathologic analysis and immunohistochemical detection of tartrate‐resistant acid phosphatase (TRAP) were also performed. Data were statistically analyzed (analysis of variance or Kruskal–Wallis, P <0.05). Results: Histometric and microtomographic analyses (at buccal, interproximal, and furcation sites) demonstrated that EP‐TIL1 presented less alveolar bone loss (ABL) than EP ( P <0.05), whereas EP‐TIL0.1 and EP‐TIL0.3 did not demonstrate significant differences in alveolar bone level compared to EP ( P >0.05). Also, EP‐TIL1 showed significantly fewer TRAP‐positive multinucleated osteoclasts than EP and EP‐Saline ( P <0.05). Conclusion: It can be concluded that locally administered TIL solution (1 mg/kg body weight) reduced alveolar bone loss in experimental periodontitis and the dosage of TIL may influence its anti‐inflammatory and antiresorptive properties.